Bearing Failure Analysis on Gearbox Forced Draft Fan at LNG Plant - Edward Rangga Pratama; Alaya Fadllu Hadi Mukhammad (Indonesian Journal of Science and Technology, 2018)
Boilers Forced Draft Fan has a gearbox reducer to reduce speed from steam turbine as a driver and fan as the driven. Based on Predictive Maintenance Group at Machinery and Heavy Equipment Section, it was found that gearbox has high vibration and noise when boilers load on 195 Ton/Hr (Max Load 295 Ton/hr). Vibration Analysis indicates that the source of vibration comes from bearings with peak value 0.572 in/sec at gearbox high speed outboard vertical and 0.593 in/sec at gearbox high speed outboard horizontal (Max Allowance 0.50 in/sec). Lubrication analysis using X-ray Flourescence method, to see wear particle on lubricating oil showed that Tin(Sn) content is very high 203.62 mg/L (maximum allowance for Tin(Sn) at gearbox is 20mg/L), but wear debris are not found in lubricating oil. Gearbox disassembly found that high speed and low speed bearings suffered severe corrosion. Corrosion at bearings are caused by water contamination on lubrication oil, it comes from steam leak due to carbon ring failure at steam turbine which is steam turbine bearing lubrication and gearbox lubrication get into one lubrication system. After Bearings replaced with a new one, vibration analysis shown improved vibration conditions 0.084 in/sec at gearbox high speed outboard vertical and 0.066 in/sec at gearbox high speed outboard horizontal. In conclucion, high vibration and noise at gearbox reducer were caused by bearings failure due to severe corrosion, and water contamination on lubrication oil for gearbox  due to carbon ring failure on steam turbine.